Impact of mental disorders on clinical outcomes of physical diseases: an umbrella review assessing population attributable fraction and generalized impact fraction. Issue 1 (14th January 2023) - Dragioti, Elena; Radua, Joaquim; Solmi, Marco; Gosling, Corentin J.; Oliver, Dominic; Lascialfari, Filippo; Ahmed, Muhammad; Cortese, Samuele; Estradé, Andrés; Arrondo, Gonzalo; Gouva, Mary; Fornaro, Michele; et al.
Abstract : Empirical evidence indicates a significant bidirectional association between mental disorders and physical diseases, but the prospective impact of mental disorders on clinical outcomes of physical diseases has not been comprehensively outlined. In this PRISMA‐ and COSMOS‐E‐compliant umbrella review, we searched PubMed, PsycINFO, Embase, and Joanna Briggs Institute Database of Systematic Reviews and Implementation Reports, up to March 15, 2022, to identify systematic reviews with meta‐analysis that examined the prospective association between any mental disorder and clinical outcomes of physical diseases. Primary outcomes were disease‐specific mortality and all‐cause mortality. Secondary outcomes were disease‐specific incidence, functioning and/or disability, symptom severity, quality of life, recurrence or progression, major cardiac events, and treatment‐related outcomes. Additional inclusion criteria were further applied to primary studies. Random effect models were employed, along with I 2 statistic, 95% prediction intervals, small‐study effects test, excess significance bias test, and risk of bias (ROBIS) assessment. Associations were classified into five credibility classes of evidence (I to IV and non‐significant) according to established criteria, complemented by sensitivity and subgroup analyses to examine the robustness of the main analysis. Statistical analysis was performed using a new package for conducting umbrella reviews (https://metaumbrella.org ). Population attributable fraction (PAF) and generalized impact fraction (GIF) were then calculated for class I‐III associations. Forty‐seven systematic reviews with meta‐analysis, encompassing 251 non‐overlapping primary studies and reporting 74 associations, were included (68% were at low risk of bias at the ROBIS assessment). Altogether, 43 primary outcomes (disease‐specific mortality: n=17; all‐cause mortality: n=26) and 31 secondary outcomes were investigated. Although 72% of associations were statistically significant (p<0.05), only two showed convincing (class I) evidence: that between depressive disorders and all‐cause mortality in patients with heart failure (hazard ratio, HR=1.44, 95% CI: 1.26‐1.65), and that between schizophrenia and cardiovascular mortality in patients with cardiovascular diseases (risk ratio, RR=1.54, 95% CI: 1.36‐1.75). Six associations showed highly suggestive (class II) evidence: those between depressive disorders and all‐cause mortality in patients with diabetes mellitus (HR=2.84, 95% CI: 2.00‐4.03) and with kidney failure (HR=1.41, 95% CI: 1.31‐1.51); that between depressive disorders and major cardiac events in patients with myocardial infarction (odds ratio, OR=1.52, 95% CI: 1.36‐1.70); that between depressive disorders and dementia in patients with diabetes mellitus (HR=2.11, 95% CI: 1.77‐2.52); that between alcohol use disorder and decompensated liver cirrhosis in patients with hepatitis C (RR=3.15, 95% CI: 2.87‐3.46); and that between schizophrenia and cancer mortality in patients with cancer (standardized mean ratio, SMR=1.74, 95% CI: 1.41‐2.15). Sensitivity/subgroup analyses confirmed these results. The largest PAFs were 30.56% (95% CI: 27.67‐33.49) for alcohol use disorder and decompensated liver cirrhosis in patients with hepatitis C, 26.81% (95% CI: 16.61‐37.67) for depressive disorders and all‐cause mortality in patients with diabetes mellitus, 13.68% (95% CI: 9.87‐17.58) for depressive disorders and major cardiac events in patients with myocardial infarction, 11.99% (95% CI: 8.29‐15.84) for schizophrenia and cardiovascular mortality in patients with cardiovascular diseases, and 11.59% (95% CI: 9.09‐14.14) for depressive disorders and all‐cause mortality in patients with kidney failure. The GIFs confirmed the preventive capacity of these associations. This umbrella review demonstrates that mental disorders increase the risk of a poor clinical outcome in several physical diseases. Prevention targeting mental disorders – particularly alcohol use disorders, depressive disorders, and schizophrenia – can reduce the incidence of adverse clinical outcomes in people with physical diseases. These findings can inform clinical practice and trans‐speciality preventive approaches cutting across psychiatric and somatic medicine.